2009
DOI: 10.1071/is08044
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships within Philodromidae, with a taxonomic revision of Philodromus subgenus Artanes in the western Palearctic (Arachnida:Araneae)

Abstract: The first quantitative phylogenetic analysis within the spider family Philodromidae (using 65 morphological characters from 40 ingroup taxa) does not corroborate Schick’s division into the tribes Thanatini (Apollophanes O. P.-Cambridge, 1898, Pelloctanes Schick, 1965, Thanatus C. L. Koch, 1837; Tibellus, Simon, 1875) and Philodromini (Ebo Keyserling, 1884, Philodromus Walckenaer, 1826; Rhysodromus Schick, 1965). Instead, Ebo is sister to all other genera in the family, and a fraction of Philodromus (the histri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 25 publications
3
40
0
2
Order By: Relevance
“…However, the leg spination pattern is strikingly diff erent, with Titanebo resembling Rhysodromus (the Philodromus histrio group) and Halodromus gen. n. Ebo and Titanebo are also diff erent in the structure of the female genitalia and in some morphometric indices (Table 1). In none of the phylogenetic analyses performed by Muster (2009) did Titanebo emerge as sister to Ebo. In conclusion, Titanebo clearly deserves generic re-establishment.…”
Section: Taxonomymentioning
confidence: 99%
See 4 more Smart Citations
“…However, the leg spination pattern is strikingly diff erent, with Titanebo resembling Rhysodromus (the Philodromus histrio group) and Halodromus gen. n. Ebo and Titanebo are also diff erent in the structure of the female genitalia and in some morphometric indices (Table 1). In none of the phylogenetic analyses performed by Muster (2009) did Titanebo emerge as sister to Ebo. In conclusion, Titanebo clearly deserves generic re-establishment.…”
Section: Taxonomymentioning
confidence: 99%
“…Th e histrio group in its current limits is most likely an artifi cial assemblage of superfi cially similar species. A recent cladistic analysis within Philodromidae (Muster 2009) has shown that histrio and related species are more closely related to the Th anatini (Th anatus and Tibellus) than to other Philodromus species groups. Th us, Rhysodromus clearly deserves re-elevation to genus rank, but the urgently required revision of the histrio group from a phylogenetic perspective is beyond the scope of this study.…”
Section: Genus Philodromus Walckenaer 1826 Ad Part (The Philodromusmentioning
confidence: 99%
See 3 more Smart Citations